SEVERE HYPONATREMIA, EPISTAXIS, AND FLUOXETINE - Kaya, Tezcan; Yücel, Murat; Eraslan, Özden; Cinemre, Hakan; Tamer, Ali (Journal of Ayub Medical College Abbottabad, 2016)
Hyponatremia is one of the most common electrolyte abnormalities and can be life threatening. Fluoxetine is a serotonin reuptake inhibitor and may rarely cause hyponatremia. Furthermore, fluoxetine may rarely increase the risk of bleeding events. We report a 66-year old woman who presented with severe hyponatremia and epistaxis associated with the use of fluoxetine.